Hydrothermal Synthesis of Ln(OH)3 Nanorods and the Conversion to Ln2O3 (Ln = Eu, Nd, Dy) Nanorods via Annealing Process. (5th December 2013) - Zhu, Yanhua; Zhai, Xiang; Wang, Lingling
Abstract : One-dimensional rare earth oxides and hydroxides are of importance in many applications due to their rich physicochemical properties. In this work, we synthesized Ln(OH)3 (Ln = Eu, Nd, Dy) nanorods by a hydrothermal method with the assistance of n-butylamine as an alkaline resource. The porous Ln2 O3 nanorods were produced through annealing the corresponding Ln(OH)3 nanorods. XRD and TEM techniques were employed to characterize the products. The annealing process and the optical properties of as-synthesized Ln2 O3 are also investigated by TG and PL test. We expected that these nanomaterials could find potential applications in the future.